Penguatan Kesehatan Mental Remaja Diaspora Melalui Seni Macrame Dan Integrasi Dakwah Islam - Nur Ulmy Mahmud; Nur Setiawati; Muhammad Ikhtiar; Andi Asrina; Nurul Ulfah Muthaliib; Andi Surahman Batara (Window of Community Dedication Journal, 2025)
Adolescents are a vulnerable age group prone to mental health problems, particularly stress and anxiety, due to academic pressures, bullying, and a lack of emotional support. This condition becomes more complex among diaspora adolescents who live in different social and cultural environments. Therefore, creative, contextual, and spiritually aligned intervention approaches are needed. This community engagement program aimed to strengthen adolescent mental health through macramé art training combined with Islamic da’wah. The activity was conducted in a one-day workshop at BP KNPI Malaysia involving 15 adolescent participants. The methods included a pre-test using the DASS-42 questionnaire, macramé training based on art therapy principles, light da’wah integration during reflection sessions, and a post-test to measure changes in mental health conditions. The results showed a reduction in stress levels by 34.1% and anxiety levels by 37.2% after the intervention. Participants also reported increased calmness, improved emotional regulation, and strengthened spiritual motivation through the values of patience, gratitude, and reliance on God emphasized during the da’wah session. Thus, art- and da’wah-based interventions proved effective as a holistic approach, addressing not only emotional aspects but also reinforcing adolescent spirituality. This program is recommended to be developed sustainably by involving community facilitators so it can become a routine initiative for adolescent mental health promotion.